Inactivation of α- and β-Thrombin by Antithrombin-III and Heparin - Machovich, Raymund; Blaskó, György; Borsodi, Anna (Thrombosis and Haemostasis, 1976)
Inactivation of α- and β-thrombin by antithrombin-III and heparin was studied, since it had been suggested that two forms of thrombin exist with respect to heparin sensitivity (Machovich 1975b).It was found that the inactivation rates of α- and β-thrombin by antithrombin were different, namely α-thrombin was more sensitive to antithrombin than β-thrombin. Heparin facilitated the complex formation between α-thrombin and antithrombin-III, whereas β-thrombin inactivation was only slightly affected.Furthermore, heparin protected α-thrombin against the inactivating effect of heat, while β-thrombin lost its activity during the heat treatment.These findings suggest that the formation of β-thrombin in blood circulation may have an important role in thrombosis predisposition.